Elevated H3K4me3 Through MLL2-WDR82 upon Hyperglycemia Causes Jagged Ligand Dependent Notch Activation to Interplay with Differentiation State of Endothelial Cells - Pandya Thakkar, Niyati; Pereira, Beatriz Maria Veloso; Katakia, Yash T.; Ramakrishnan, Shyam Kumar; Thakar, Sumukh; Sakhuja, Ashima; Rajeev, Gayathry; Soorya, S.; Thieme, Karina; Majumder, Syamantak (Frontiers in Cell and Developmental Biology, 2022)
Endothelial-to-mesenchymal transition (EndMT) is a hallmark of diabetes associated vascular complications. Epigenetic mechanisms emerged as one of the key pathways to regulate diabetes associated complications. In the current study, we aimed to determine how abrupt changes in histone 3 lysine 4 tri-methylation (H3K4me3) upon hyperglycemia exposure reprograms endothelial cells to undergo EndMT. Through in vitro studies, we first established that intermittent high glucose exposure to EC most potently induced partial mesenchyme like characteristic in compared to transient or constant high glucose challenged endothelial cells. In addition, glomerular endothelial cells of BTBR Ob/Ob mice also exhibited mesenchymal like characteristic. Intermittent hyperglycemia dependent induction of partial mesenchyme like phenotype of endothelial cells coincided with an increase in H3K4me3 level in both macro- and micro-vascular EC due to selective increase in MLL2 and WDR82 protein of SET1/COMPASS complex. Such endothelial specific heightened H3K4me3 level was also detected in intermittent high glucose exposed rat aorta and in kidney glomeruli of Ob/Ob mice. Elevated H3K4me3 enriched in the promoter regions of Notch ligands Jagged1 and Jagged2 thus causing abrupt expression of these ligands and concomitant activation of Notch signaling upon intermittent hyperglycemia challenge. Pharmacological inhibition and/or knockdown of MLL2 in cells in vitro or in tissues ex vivo normalized intermittent high glucose mediated increase in H3K4me3 level and further reversed Jagged1 and Jagged2 expression, Notch activation and EndMTfurther attenuated acquisition of partial mesenchyme like phenotype of endothelial cells. In summary, the present study identified a crucial role of histone methylation in hyperglycemia dependent reprograming of endothelial cells to undergo mesenchymal transition and indicated that epigenetic pathways contribute to diabetes associated vascular complications.